2015
DOI: 10.1186/s12917-015-0359-z
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and antiviral activity of mink alpha-interferons

Abstract: BackgroundAs a key link between innate and adaptive immune responses, the interferon (IFN) system is the first line of defense against viral infection. IFN, and in particular, IFN-α, has been used clinically as an effective therapeutic agent for viral infections. However, different subtypes of IFN-α demonstrate distinct antiviral activity. Therefore, it is important to identify IFN-α subtypes with high antiviral activity for the development of genetically engineered antiviral drugs.ResultsIn this study, we clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In recent years, mink distemper, mink parvovirus enteritis, aeutian disease and other infectious diseases have been endangering the survival of mink Zhang et al, 2015). Thus, the prevention and treatment of these diseases cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mink distemper, mink parvovirus enteritis, aeutian disease and other infectious diseases have been endangering the survival of mink Zhang et al, 2015). Thus, the prevention and treatment of these diseases cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Imidazole was removed by dialysis against PBS. Western blotting of the partially purified 6 × His-tagged IFN-α was performed as described previously ( 10 ). The purified protein was quantified with the bicinchoninic acid (BCA) protein assay kit using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Blood was collected from the tail vein at 0 h, 15 min, 30 min, and 1, 2, 4, 6, 8, 12, 24, 36, 48, 72, 96, 108, 132, and 156 h after injection, and serum was obtained by centrifugation at 4,000 rpm for 20 min at 4°C. As no commercial mink IFN-α detection kit was available, and mink and canine IFN-α share 80.9% homology at the nucleotide sequence ( 10 ), serum MiIFN-α was quantified using canine IFN alpha-1/2 (IFN-α1/2) ELISA (Abebio, China). Western blot experiments confirmed that canine IFN-α monoclonal antibody can cross-react with mink IFN-α, and thus, we used the commercial canine IFN-α ELISA kit to detect mink IFN-α in rat serum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the IFN-α proteins encoded by humans and other animal species are all highly effective in limiting virus replication and spread [ 4 , 5 , 6 , 7 ]. Although IFNs are broad-spectrum antiviral agents, the sequence conservation of the IFN-α proteins from different species can differ considerably [ 8 , 9 ], and there are also differences in the potency of different IFN-a homologues [ 10 , 11 ]. The antiviral property of goat IFN-α has not been evaluated for prophylaxis and/or therapeutic treatment of viral infections to date.…”
Section: Introductionmentioning
confidence: 99%